“Unta Mu-Ulan”: The Social Sustainability of Lowland Rice Farmers in Iligan City Amid the Consequences of Climate Change - Sumaylo, Sasha Roi B.; Torres, Ceejay R.; Vios, Roscel Kent T.; Palomares, Perla P. (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2025)
This study seeks to determine whether the lowland rice farmers of Iligan City are socially sustainable by looking at their lived experiences, their engage- ment with local policy-making, and the government’s support towards them. The study used a qualitative research design employing a case study method on three farmers’ associations in the city. Purposive sampling is utilized for selecting the respondents, whereby the rice farmers and the relevant local government officials, and CSOs have undergone KIIs. In contrast, the officers of the cited farmers’ associations: TUFA, SUFA, and ZRFWA, underwent FGDs. Thematic analysis is then utilized to treat the data. The inquiry into the farm- ers’ lived experiences revealed the human cost of ineffective government support, where laws fail to translate into sufficient tangible benefits for the farmers, and sentiments reflecting eroded trust and isolationism inevitably arise when they feel unheard. With politicking and resource constraints crip- pling their policy influence, stringent eligibility criteria for government support hindering them from getting any; and reactive, short-term solutions failing to address their susceptibility to climate change— the farmers’ welfare is, there- fore, trapped in a cycle of ayuda or governmental temporary reliefs. The study found that the local government policies have demonstrably failed to achieve social sustainability for the lowland rice farmers.